QUALITATIVE RESEARCH: RELATIONSHIP CUSTOMER LOYALTY WITH CUSTOMER SATISFACTION, CO-CREATION, PRODUCT INNOVATION, AND SOCIAL MEDIA MARKETING - Hanafiah, Hafidz; Gursida, Hari; Muharam, Hari (Yayasan Education and Social Center, 2025)
Loyalty is one form of attitude and behavior of customers. Customer loyalty is formed by going through several stages based on customer experience, exceeding satisfaction, and always being loyal. However, customer loyalty will change when there is a weakness in implementing a customer loyalty program as a medium for the sustainability of loyalty itself. Not committed and inconsistent in carrying out this loyalty, the tendency for business sustainability will change slightly when accustomed to having loyal customers. The purpose of this study with a literature review of the influence of several variables on customer loyalty is studied. The research method is qualitative which comes from book and journal references related to the theme being studied. The results of the study found that customer loyalty is influenced by customer satisfaction, co-creation, product innovation, and social media marketing. Then customer satisfaction is also influenced by co-creation, product innovation, and social media marketing. As well as co-creation, product innovation, and social media marketing each affect customer loyalty through customer satisfaction. So that loyalty can provide a positive atmosphere for business actors. Further research suggestions need to be conducted quantitatively and research objects in detail